Students’ Perception on the Role of Practitioner-Tutors in the Design Studio - Kusumowidagdo, Astrid (Humaniora, 2019)
This research explored the perception of the students on the role of practitioner-tutors in the learning process of the Design Studio courses. Practitioner-tutors were commonly employed in the learning process at university and generally provided a collaborative contribution for the teaching team of lecturers or persons in charge of the design studios. The research utilized the quantitative method with surveys and was analyzed using the descriptive statistics method. The objects of the research were twenty practitioner-tutors in four design studios, and the respondents were a hundred students from various years of study. The research variables of the roles of practitioner-tutors included learning goal orientation, feedback seeking, help-seeking, and behavior learning engagement. In conclusion, the research shows that students perceive the role of the practitioner-tutors in the four dimensions as quite good, with the highest merits being, in consecutive order, learning goal orientation and feedback seeking. Meanwhile, help-seeking and behavior learning engagement variables both are placed last with the same value. The benefit of this research is applied to the design studio course manager, and tutors for the better process of tutoring in a design studio course and giving the foundation for further similar research.